Isolation, Morphological and Biochemical Characterization of Culturable Endophytic Microflora in Paris polyphylla Sm. from Nepal - Rashal Shakya; Samriddhi Bhochhibhoya; Sanchit Regmi; Rabin Pokhrel; Aanande Ghalan; Tara Shrestha; Bishnu Maya KC; Dhurva Prasad Gauchan (Nepal Journal of Biotechnology)
Paris polyphylla Sm., also known as “Satuwa” in Nepal is a perennial medicinal herb, endemic to the Himalayan region. The plant is known to produce numerous bioactive compounds and provide medicinal use. Presently, it is in a state of vulnerability due to overexploitation, lower rate of seed germination, overharvesting, fragmentation of lands, and deforestation. Endophytic microbes of P. polyphylla. have been shown to produce numerous bioactive compounds in correspondence to the host plant. As there have been very few studies of Paris species in Nepal this study strives to explore the potential of the endophytic variety in the endemic species. The study investigated the endophytic microbiome in the rhizomes of the species from Dhunkharka, Nepal. A total of 18 endophytic bacterial isolates and 5 fungal isolates were obtained from the rhizome of P. polyphylla. Several isolates showed distinct morphological forms and were characterized using Gram staining, endospore staining, IMViC tests, catalase test, motility test, and triple sugar agar test. Among the endophytic bacterial isolates, 11 isolates showed gram-positive results and 5 were gram-negative, while endospore staining showed 10 negative and 6 positive isolates. Among the bacterial isolates, 6 were Methyl-Red (MR) positive, 2 were Voges-Proskauer (VP) positive, 15 isolates showed positive motility test, 10 were catalase-positive and 6 were citrate-positive. The fungal isolates could belong to the phylum Ascomycetes based on macroscopic and microscopic analysis. Further molecular characterizations are needed to accurately identify the endophytic isolates. The findings hint that these endophytic microorganisms could be a viable alternative for producing secondary metabolites, aiding in the conservation and medicinal use of the vulnerable P. polyphylla.